Chumleafel Chi Anültuzugu Chile Mapu Mew: The Role of Mapuzugun in the Chilean Constituent Process (2019-2022); [Chumleafel Chi Anültuzugu Chile Mapu Mew: El Papel del Mapuzugun en el Proceso Constituyente Chileno (2019-2022)] - Loncon-Antileo, E (Ediciones Universitarias de Valparaiso, 2023)
This article examines the role played by mapuzugun in the first Chilean constituent process. Specifically, it describes how mapuzugun expanded to new contexts of use in three stages of this process—the social outbreak, the Constitutional Convention, and the drafting of the new Constitutional proposal—and assesses this phenomenon regarding the normalization process of this indigenous language. To that end, a single case study was carried out in order to characterize the new discourse practices where mapuzugun is employed, to identify the social functions performed, and to evaluate the way the language has changed to accommodate to these new communicative uses. The analysis shows that mapuzugun increased its presence in a specialized legislative context and changed its status, because it was recognized as official language of the Constitutional Convention, a political body of the Chilean State. These advances are crucial for the process of mapuzugun normalization. However, they were carried out in an unplanned manner, so there is a high risk that these new discourse spaces might get lost and do not consolidate among speakers. For that reason, it is necessary that indigenous languages are granted legal recognition and that material conditions are guaranteed to enable speakers to use their languages in these new spaces. © (2023) PUCV, Chile.